The human affectome - Schiller, Daniela; Yu, Alessandra N.C.; Alia-Klein, Nelly; Becker, Susanne; Cromwell, Howard C.; Dolcos, Florin; Eslinger, Paul J.; Frewen, Paul; Kemp, Andrew H.; Pace-Schott, Edward F.; Raber, Jacob; Silton, Rebecca L.; et al. (Neuroscience & biobehavioral reviews, 2024)
Over the last decades, theoretical perspectives in the interdisciplinary field of the affective sciences have proliferated rather than converged due to differing assumptions about what human affective phenomena are and how they work. These metaphysical and mechanistic assumptions, shaped by academic context and values, have dictated affective constructs and operationalizations. However, an assumption about the purpose of affective phenomena can guide us to a common set of metaphysical and mechanistic assumptions. In this capstone paper, we home in on a nested teleological principle for human affective phenomena in order to synthesize metaphysical and mechanistic assumptions. Under this framework, human affective phenomena can collectively be considered algorithms that either adjust based on the human comfort zone (affective concerns) or monitor those adaptive processes (affective features). This teleologically-grounded framework offers a principled agenda and launchpad for both organizing existing perspectives and generating new ones. Ultimately, we hope the Human Affectome brings us a step closer to not only an integrated understanding of human affective phenomena, but an integrated field for affective research.